La verdad de los hechos en el proceso judicial - Celis Vela, Dúber Armando (2023)
This paper aims to analyze the theoretical, factual, and legal di fficulties that arise when studying legal proceedings on epistemological grounds. The nature of facts within the framework of trials is determined by the parties’ claims, procedural requirements and the purpose of evidence. Therefore, it is difficult to sa tisfy fully the quest for truth in a judicial opinion because it depends on variables that cannot be controlled by those who participate in the proceedings. Thus, assessing evidence involves a confrontation of personal interests and it is in turn dependent upon the reconstruction of facts in a legal process.